A comparative study on the effects of electron beam irradiation on imidacloprid-resistant and -susceptible Aphis gossypii (Hemiptera: Aphididae). (July 2015) - Yun, Seung-Hwan; Koo, Hyun-Na; Lee, Seon-Woo; Kim, Hyun Kyung; Kim, Yuri; Han, Bumsoo; Kim, Gil-Hah
Abstract: The melon and cotton aphid, Aphis gossypii, is a polyphagous insect pest. This study compared the development, reproduction, DNA damage, recovery, and gene expression in imidacloprid-resistant (IMI-R) and -susceptible (S) strains of A. gossypii by electron beam irradiation. When 1st instar nymphs were irradiated with 100 Gy, the fecundity (nymphs of F 1 generation) of the resultant adults were completely inhibited. When adults were irradiated with 200 Gy, the number of total 1st instar nymphs produced per adult was 3.0±1.7 and 1.9±1.4 in the S and IMI-R strains, respectively, but adult development was completely suppressed. However, electron beam irradiation did not affect adult longevity in either the S or IMI-R strain. There was no statistically significant difference between the effect of irradiation on the S and IMI-R strains. Therefore, electron beam irradiation at 200 Gy could be used as a phytosanitary irradiation treatment for both S and IMI-R strains of A. gossypii . The DNA damage caused by electron beam irradiation was evaluated by an alkaline comet assay. Exposure to an electron beam (50 Gy) induced DNA damage that was repaired to a similar level as the untreated control group (0 Gy) over time. However, at more than 100 Gy, the DNA damage was not completely repaired. The expression of P450, HSP70, cuticle protein, and elongation factor genes were higher in the IMI-R strain than in the S strain. Highlights: Electron beam irradiation induces abnormal development in both the IMI-R and -S strain. Electron beam irradiation induces DNA damage in both the S and IMI-R strain. The expression of several specific genes were higher in the IMI-R strain. 200 Gy could be used as a phytosanitary treatment for both strains of this species.